Gestão do nível de gás de cozinha (GLP) - Chagas, Marcos Rezende (2018)
This work presents a gas cylinder pressure level monitoring system prototype, aiming to predict the replacement schedule. This measurement is done by a digital pressure sensor, which sends the information using WiFi to a cloud-connected database. This database will provide the information to an Android App, which presents real time status of the pressure level inside the cylinder.